A Call to Action for Video Game Studies in an Age of Reanimated White Supremacy - Russworm, Treaandrea M. (The Velvet Light Trap, 2018)
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Computational Blackness: The Procedural Logics of Race, Game, and Cinema, or How Spike Lee's Livin' Da Dream Productively "Broke" a Popular Video Game - Russworm, TreaAndrea M. (Black Camera, 2018)
How have video games evolved to now create meaningful stories about race and sports? This essay examines how Spike Lee's film-within-a-game, Livin' Da Dream (2015), reproduces some existing procedural and racial logics that reflect the desire to constantly manage and contain the centrality of black athletic greatness in mainstream sports and video game culture. While Lee's long-form cinematic model for turning sports video games into narrative games has been emulated across the medium as a whole, fans and gamers continually discuss the film as an evidently "broken" part of the popular NBA 2K video game series. As I argue here, however, the film-within-a-game productively insists on a default blackness when it functions as what I call "procedural cinema" (a rules and process based narrative). Ultimately, in functioning procedurally, Lee's otherwise conservative melodramatic story serves as a particularly instructive example of how computational blackness may, in systematically subverting the rules of the game, signify disruptively both within and against the machine.
Keywords: 1-Cinéma; 1-Jeux vidéo; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé; _À nettoyer; _À vérifier-Cinéma

Video Game History and the Fact of Blackness - Russworm, TreaAndrea M. (ROMchip, 2019)
Video games studies, including many of our most inspired written accounts of video game history, is very white. Stories about US video game pioneers, from engineers and designers to early adopters and arcade patrons, tend to be mostly about the white men who created, consumed, and periodically saved the industry. Even now that game history is on the verge of becoming as queer and ostensibly nonconformist as some aspects of its games and culture are theorized to be, these new avenues of critical investigation speak most directly to a queer mainstream that has always been constructed as white. Although there is much to be inspired by in the proliferation of emergent video game histories that are more gender-inclusive, trans, or so-called diverse, with few exceptions these progressive accounts still tend to be White. White. White. Black designers, players, blerds, and technocrats have been excluded from the canon of old and new video game histories in much the same way Frantz Fanon theorized that blackness functions as a fact: an outwardly defined pejorative social inscription that justifies its alienation and exclusion.
Number: 1
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Gaming Representation: Race, Gender, and Sexuality in Video Games - Malkowski, Jennifer; Russworm, TreaAndrea M. (Indiana University Press, 2017)
Gaming Representation' offers a timely and interdisciplinary call for greater inclusivity in video games. The issue of equality transcends the current focus in the field of Game Studies on code, materiality, and platforms. Journalists and bloggers have begun to hold the digital game industry and culture accountable for the discrimination routinely endured by female gamers, queer gamers, and gamers of color. Video game developers are responding to these critiques, but scholarly discussion of representation in games has lagged behind. Contributors to this volume examine portrayals of race, gender, and sexuality in a range of games, from casuals like Diner Dash, to indies like Journey and The Binding of Isaac, to mainstream games from the Grand Theft Auto, BioShock, Spec Ops, The Last of Us, and Max Payne franchises. Arguing that representation and identity function as systems in games that share a stronger connection to code and platforms than it may first appear, 'Gaming Representation' pushes gaming scholarship to new levels of inquiry, theorizing, and imagination.
Google-Books-ID: qJwRvgAACAAJ
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Europe (lieu de production du savoir); 5-Auteur.rice LGBTQ+; 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; 5-Autrice; 5-Créatrice; _Nettoyé